A basic review on the inferior alveolar nerve block techniques - Khalil, Hesham (Medknow Publications & Media Pvt Ltd, 2014)
The inferior alveolar nerve block is the most common injection technique used in dentistry and many modifications of the conventional nerve block have been recently described in the literature. Selecting the best technique by the dentist or surgeon depends on many factors including the success rate and complications related to the selected technique. Dentists should be aware of the available current modifications of the inferior alveolar nerve block techniques in order to effectively choose between these modifications. Some operators may encounter difficulty in identifying the anatomical landmarks which are useful in applying the inferior alveolar nerve block and rely instead on assumptions as to where the needle should be positioned. Such assumptions can lead to failure and the failure rate of inferior alveolar nerve block has been reported to be 20-25% which is considered very high. In this basic review, the anatomical details of the inferior alveolar nerve will be given together with a description of its both conventional and modified blocking techniques; in addition, an overview of the complications which may result from the application of this important technique will be mentioned.